Answer:
Nolan is correct.
Step-by-step explanation:
Here's a picture that might help you understand...
If you still need help understanding, I'll explain myself.
I hope this helps you
at the 30-60-90 triangle has rules
30=>k
60=>k(square root of) 3
90=>2k
so in this triangle 60=> see 9
k(square root of) 3=9
k=9/(square root of) 3
2k=18/(square root of) 3
at the 45-45-90 triangle rules are
45=>2k
45=>2k
90=>[2k/(square root of 3)] (square root of) 2
x=[18/(square root of 3)].(square root of 2)
x=18(square root of 2)/square root of 3
The new coords are (2,-3) the new y coord is -3
Answer: the answer is 35.1
Step-by-step explanation: